“HOMO AXIOLOGICUS” DIMENSI FENOMENOLOGIS DAN ONTOLOGIS NILAI - Gunawan, L.A.S.; Tinambunan, Laurentius; Antono, Yustinus Slamet (UNIKA Santo Thomas, 2025)
Homo axiologicus starts from the concept of human nature as a thoughtful animal (animal rationale). Human beings are part of the animal kingdom, but they transcend it due to their capacity for thinking. By thought, humans differentiate themselves from other animals. One key distinction is their ability to engage with and live by values, which is what defines homo axiologicus. This article aims to explain the phenomenological and ontological dimensions of value. The phenomenological dimension deals with how values appear or present themselves in human experience. The central question posed here is: How do values appear in human consciousness? Furthermore, the ontological dimension concerns the existence and nature of values, addressing questions such as: What are values? How do values exist? Where do values originate? Through these two dimensions, values in human consciousness possess two aspects: on one hand, values manifest in daily life and academic life; on the other hand, the values that appear in consciousness have an essential foundation. Therefore, values in the life of homo axiologicus present themselves existentially through both the phenomenological and ontological dimensions, demonstrating that human beings are rational beings as well as volitional beings in the world.